A review of the energy–carbon–water nexus: Concepts, research focuses, mechanisms, and methodologies. Issue 1 (16th July 2019) - Li, Hao; Zhao, Yuhuan; Lin, Jiang
Abstract: The energy–carbon–water (ECW) nexus has aroused increasing attention worldwide, as it is very important for sustainable development of socioeconomic systems. Researchers conducted a literature review of existing studies on the ECW nexus in terms of concepts, research focuses, mechanisms, and methodologies. Current research on the ECW nexus mainly focuses on the ECW flow accounting, the impact assessment of ECW‐related policies or measures, and the description of the nexus characteristics. ECW‐related measures may lead to a variety of cobenefits: economic growth, pollutant reduction, water quality improvement, and the carbon–water trade‐off—that is, that the adoption of water‐saving cooling technologies (such as wet cooling) could increase energy use and carbon dioxide (CO2 ) emissions. ECW‐related measures could also lead to the deployment of some low‐carbon power generation technologies, such as hydro, nuclear, and biofuel that could increase power sector water use. Nexus mechanisms of existing studies are mainly aimed at a specific sector; fewer studies consider the mechanisms from an economy‐wide perspective. Integrated models, such as computable general equilibrium‐based models and input–output (IO)‐based hybrid life cycle assessment models, should be used to assess the broad socioeconomic impacts of ECW‐related measures in future, in order to inspire policymakers to design and implement effective measures for integrated ECW management. This article is categorized under: Energy and Climate > Economics and Policy Concentrating Solar Power > Climate and Environment Abstract : The energy‐carbon‐water (ECW) nexus mechanism of a simplified economy system.